UPAYA KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MADRASAH ALIYAH ANWARUL ULUM DESA LINTAS UTARA KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Nur Komariah; Astutik Astutik (Fakultas Ilmu Agama Islam Universitas Indragiri, 2020)
This study aims to determine the extent of the principal's efforts in improving teacher performance, obstacles encountered and solutions developed for the obstacles encountered. This study uses a qualitative approach, with data collection methods of observation, interviews and documentation. The results of this study are the principal has made several efforts to improve teacher performance optimally. But there are still a number of obstacles namely there are still teachers who do not have the discipline and limitations of teachers in mastering IT. The solution to this problem, the headmaster gave computer training to teachers who were known to not yet have the skills to operate a computer, gave rewords to high achievers and gave the opportunity for all teachers to attend religious tours to visit the trustees' meals.